Houses as ATMs: Mortgage Refinancing and Macroeconomic Uncertainty - CHEN, HUI; MICHAUX, MICHAEL; ROUSSANOV, NIKOLAI (Journal of Finance, 2020)
ABSTRACT Mortgage refinancing activity associated with extraction of home equity contains a strongly countercyclical component consistent with household demand for liquidity. We estimate a structural model of liquidity management featuring countercyclical idiosyncratic labor income uncertainty, long‐ and short‐term mortgages, and realistic borrowing constraints. We empirically evaluate its predictions for households' choices of leverage, liquid assets, and mortgage refinancing using microlevel data. Taking the observed historical paths of house prices, aggregate income, and interest rates as given, the model accounts for many salient features in the evolution of balance sheets and consumption in the cross‐section of households over 2001 to 2012.